Psychiatric Symptomatology, Mood Regulation, and Resting State Functional Connectivity of the Amygdala: Preliminary Findings in Youth With Mood Disorders and Childhood Trauma - Dvir, Yael; Kennedy, David N.; Hodge, Steven M.; Pegram, Destiny; Denietolis, Brian; Frazier, Jean A. (Frontiers in Psychiatry, 2020)
Background: As mood dysregulation and hyperarousal are overlapping and prominent features of Posttraumatic Stress Disorder (PTSD), and Mood Disorders (MD) including Bipolar Disorder (BD), we aimed to clarify the role of trauma and MD on resting state functional connectivity (RSFC) of amygdala in MD youth with or without trauma exposure, and healthy controls (HC). Methods: Of 23 subjects, 21 completed the magnetic resonance imaging (MRI) protocol, 5 were excluded for subject motion, leaving final sample size of 16: nine subjects with MD (5/9 with trauma), and 7 HC. Youth were assessed with Schedule for Affective Disorders and Schizophrenia for School Aged Children – Present and Lifetime Version (K-SADS-PL), and other behavioral measures including Young Mania Rating Scale (YMRS). Imaging data were acquired using functional MRI in 3-T scanner. Imaging included T1-weighted structural MRI and 6-minute resting state acquisition. Results: In between group analysis, the average correlation coefficients between Left Anterior Cingulate (ACC) and Left Insula cortex with Left Amygdala regions were significantly larger in HC compared to the patient population. Connectivity between Left Amygdala and Left Cingulate cortex shows a significant negative correlation with YMRS severity. Conclusions: MD with trauma youth had more manic symptoms and difficulties regulating anger. While MD youth showed reduced RSFC of Left Amygdala with Left ACC and Left Insula, no significant difference between the subgroups of children with MD was observed. However, when looking at both clinical groups together, we observed a significant correlation of RSFC of Left Amygdala to Left ACC, and YMRS scores.